Employee Performance Through Improved Teamwork and Training at Lv8 Resort Hotel - Aristana, I Nengah; Artana, I Wayan Arta; Yasa, I Wayan Dita (Universitas Pamulang, 2022)
The hotel industry before the COVID-19 pandemic experienced rapid development and growth. This study aims to analyze the effect of teamwork and training on employee performance at Lv8 Resort Hotel and the role of training as a mediator on the effect of teamwork on employee performance. This research was conducted at Lv8 Resort Hotel and data collection using a questionnaire. The research population is all employees who work at Lv8 Resort Hotel. The method of determining the sample using saturated sampling. All data collected using SEM-PLS analysis technique with Smart PLS 3.0. The results of this study indicate that teamwork and training have a positive and significant effect on employee performance, training has a positive and significant effect on employee performance and training acts as a partial mediator of the effect of teamwork on employee performance.